FORECASTING THE ACCURACY CHARACTERISTICS OF AUTOMATIC AIRCRAFT SYSTEMS - Махновський, Б. Г.; Зеленков, О. А. (Proceedings of National Aviation University (archive), 2021)
The question of organizational and mathematical support of forecasting of a condition of systems of automatic landing of planes on realizations of defining parameters of landing is considered. The algorithm for determining the forecast characteristics is given.